As redes sociais digitais e a ampliação do horizonte valorativo - Corazza, Maritana (2019)
This research proposed reflexions delimited on the enunciation of two subjects that actively participate in social networks through discourse, appropriating new layers of words and new meanings in different contexts, thus broadening its value horizon, from this, constituting itself as subject. The objective that mobilizes this research is to analyze the magnification of the value horizon in interactions experienced by an interior couple. The conceptions of enunciation, interaction, ideological sign, theme and signification are ess entially pondered by Volóchinov/Bakhtin (2017) and to better understand it, we anchor ourselves in their scholars Brait and Melo (2017), Cherry (2017), Faraco (2009), Ponzio (2009) and Sobral (2017), being the theoretical framework that composes the first and second pillar on which this study covers. To explore the relevance of the study of discursive genres the theoretical basis is guided mainly by Bakhtin (2016) and his scholars Faraco (2009), Machado (2017), Marcuschi (2008) and Sobral (2017) forming the third pillar of this research, which explains the presence and use of ideological signs in different interactive supports that through the theme, language style and compositional construction, find the different ways of meaning. The corpus of this research comes from the discourse composed in some representative enunciative cuts of the subjects of this research, which encompasses the extension of the value horizon through words arising from the interaction in digital social networks that are fundamental for the constitution of these subjects. The research is characterized, as far as the objectives, as exploratory and descriptive; field research with regard to enunciative cuts to be explored; bibliographical, as for the technical procedures and is classified, by its approach, as qualitative. The possible results show that the magnification of the value horizon of the subjects does not only consist in the exploration of some words and their sharing, but rather in the new way of meaning that each individual performs by making use of the ideological sign to communicate, adjusting to the theme of each statement to understand the meaning of the word. For the moment, we admit that social networks are responsible for the constitution of the subject, so that the statements present in the digital environments contribute, through the interaction between users, an extension of the value horizon, and causes this to participate in discourse shared by the interacting subjects of a society that shares the same ideology.